Breastfeeding problems: an analysis of secondary data from Lactation Management Unit at the national referral hospital in Bhutan from 2014 to 2016 - Kencho Zangmo; Diki Wangmo; Tashi Tobgay; Mongal S. Gurung (Bhutan Health Journal, 2018)
Introduction: Breastfeeding is one of the most natural and best forms of preventive medicine for the newborns. Lack of optimal breastfeeding contributes to about over million preventable child deaths every year. Despite numerous benefits of breastfeeding and continuous efforts to improve breastfeeding practices, breastfeeding rates are far from optimal. Problems faced by lactating mothers while breastfeeding are main reason leading to non-exclusive breastfeeding or early termination of breastfeeding. This descriptive study is aimed at examining breastfeeding problems among women visiting Lactation Management Unit [LMU] at Bhutan’s national referral hospital in Thimphu.